Complete anterior circle of Willis improves thrombectomy efficacy of balloon guide catheter for internal carotid artery occlusion - Chen, Yigang; Jin, Xing; Shi, Feina; Jiang, Yun; Hu, Beibei; Zheng, Xu; Zhang, Jinhua (Frontiers in Neurology, 2025)
IntroductionWith the continuous advancement of clinical techniques, the role of the balloon guide catheter (BGC), in practice, has gradually diminished. However, identifying anatomical factors associated with its therapeutic efficacy remains essential. Variations in the configuration of the circle of Willis (CoW) can lead to distinct hemodynamic changes. This study aimed to evaluate the effectiveness of the use of BGC during anterior circulation thrombectomy across different CoW configurations.MethodsThis single-center retrospective study analyzed 109 patients admitted with embolic large vessel occlusion (LVO) of the anterior circulation. A complete anterior CoW was defined as the presence of a patent anterior communicating artery (ACoA) and bilateral A1 segments. We assessed the single-pass recanalization rate, the recanalization rate within two passes, and the procedure time associated with BGC use across different anterior CoW configurations.ResultsOf the 45 patients with a complete anterior CoW, this configuration was associated with a higher single-pass recanalization rate (48.9 vs. 28.1%, p = 0.027) and a shorter procedure time (58.4 vs. 82.8 min, p = 0.005). In the subgroup analysis, the use of BGC in cases of internal carotid artery (ICA) occlusion with a complete anterior CoW achieved the highest single-pass recanalization rate (61.9%) and recanalization within two passes (95.2%). Logistic regression analysis demonstrated that the BGC use in ICA occlusion with a complete anterior CoW was an independent factor associated with a higher likelihood of achieving recanalization within two passes (p = 0.001).ConclusionA complete anterior CoW was an independent factor associated with fewer thrombectomy passes and a shorter procedure time. For patients with ICA occlusion and a complete anterior CoW, the use of BGC was the optimal approach to improve overall thrombectomy efficacy.